Opioid-Associated Out-of-Hospital Cardiac Arrest: Distinctive Clinical Features and Implications for Health Care and Public Responses. Issue 16 (20th April 2021) - Dezfulian, Cameron; Orkin, Aaron M.; Maron, Bradley A.; Elmer, Jonathan; Girotra, Saket; Gladwin, Mark T.; Merchant, Raina M.; Panchal, Ashish R.; Perman, Sarah M.; Starks, Monique Anderson; van Diepen, Sean; Lavonas, Eric J.
Abstract : Opioid overdose is the leading cause of death for Americans 25 to 64 years of age, and opioid use disorder affects >2 million Americans. The epidemiology of opioid-associated out-of-hospital cardiac arrest in the United States is changing rapidly, with exponential increases in death resulting from synthetic opioids and linear increases in heroin deaths more than offsetting modest reductions in deaths from prescription opioids. The pathophysiology of polysubstance toxidromes involving opioids, asphyxial death, and prolonged hypoxemia leading to global ischemia (cardiac arrest) differs from that of sudden cardiac arrest. People who use opioids may also develop bacteremia, central nervous system vasculitis and leukoencephalopathy, torsades de pointes, pulmonary vasculopathy, and pulmonary edema. Emergency management of opioid poisoning requires recognition by the lay public or emergency dispatchers, prompt emergency response, and effective ventilation coupled to compressions in the setting of opioid-associated out-of-hospital cardiac arrest. Effective ventilation is challenging to teach, whereas naloxone, an opioid antagonist, can be administered by emergency medical personnel, trained laypeople, and the general public with dispatcher instruction to prevent cardiac arrest. Opioid education and naloxone distributions programs have been developed to teach people who are likely to encounter a person with opioid poisoning how to administer naloxone, deliver high-quality compressions, and perform rescue breathing. Current American Heart Association recommendations call for laypeople and others who cannot reliably establish the presence of a pulse to initiate cardiopulmonary resuscitation in any individual who is unconscious and not breathing normally; if opioid overdose is suspected, naloxone should also be administered. Secondary prevention, including counseling, opioid overdose education with take-home naloxone, and medication for opioid use disorder, is important to prevent recurrent opioid overdose. Abstract : Supplemental Digital Content is available in the text.